The role of Public and private university libraries in the application of cloud computing services from the point of view of their employees in Irbid Governorate - Saleem, Tayseer Andrawes (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the role of public and private university libraries in the application of cloud computing services from the point of view of their employees, where the study sample consisted of (87) members. As for the study tool, it was represented by the questionnaire prepared by the researcher, which included (25) paragraphs after verifying its psychometric properties. The study was conducted and necessary statistical treatments showed that the arithmetic averages of the study sample ranged between high and medium. However, the overall rate was average. The views of librarians focused on a group of cloud computing applications related to e-mail services, public relations, reference services, publishing, and marketing programs via the Internet, Office 365, Google scholar services, and Geographic information system (GIS) services. The results of the hypotheses examination revealed that there are statistically significant differences in the tool as a whole according to the variable (university) and in favor of workers in public universities, and those with (scientific qualifications / postgraduate studies). The study concluded by emphasizing that cloud computing is the future, and the world is heading towards it, despite the challenges facing its application, and the need to conduct more similar studies in other public and private university libraries.